Build Encrypted Interconnection Networks by application of IP Security and Mac Address Filtering Authentication Methods: بناء شبكات ربط مشفرة من خلال تطبيق أساليب مصادقة أمان IP وتصفية عنوان Mac - Jouma Ali AlMohamad (Journal of engineering sciences and information technology, 2021)
To improve the security in data networks we use of IP Security and MAC Address Filtering authentication methods on network devices is very useful to be able to protect, verify and filter company data especially if data contain sensitive information like credit cards while using public data network. IP Security authentication provides integrity between connections, then Filtering MAC Address can help the router task to be able recognize users on the network, So that expected the combination between IP Security and Mac Address Filtering will provide security for every transfer and receive data from Headquarter to branch office, then the company doesn’t have to worry about data package being robbed or manipulated by the unauthorized parties.